The Issuer Recognition program at the Colombian Stock Exchange: An unknown corporate governance hybrid model of hard and soft law (2020)
Research Question/Issue: What is the Issuer Recognition (IR) program, and what has been its impact as a new and replicable corporate governance hybrid form used in the Colombian Stock Ex-change (CSE)?